Teacher Professional Development in Developing English Assessments Through TPACK - Fauris Zuhri (Universitas Pendidikan Indonesia, 2022)
Exploring teacher professional development requires two main teaching factors in the digital era. They are internal factors and external. In internal, the teacher plays an essential role in developing professionalism in teaching. In shallow, it is teaching instruments – lesson plans. The appropriate English teacher and lesson plan development contribute significantly to teaching achievement. Therefore, this study explores how English teachers implement technological pedagogical and content knowledge to improve their English instructional assessments in teacher professional development. Implementing technical pedagogical and content knowledge in teacher professional development can gradually enhance their English instructional evaluations. They have different language competencies backgrounds by progressively implementing technological pedagogical and content knowledge in teacher professional development. Still, they can improve their English instructional assessments. The study uses a survey: a questionnaire, interviews, and observation are applied to find the data. The subjects are English teachers who joined teacher professional development in Surabaya 2020. The research results showed that implementing technological pedagogical and content knowledge can improve English instructional assessments in teacher professional development. Three factors contribute to integrating English instructional assessment with technical pedagogical and content knowledge. English teachers are more comfortable making English instructional assessments, alternative instructional English evaluations are available, and improved English instructional reviews. Therefore, English instructional evaluations are more exciting and challenging. Thus, integrating English instructional assessments with technological pedagogical and content knowledge in teacher professional development is crucial in improving teaching English in Indonesia.